Reterritorialiser les stéréotypes latino-américains : comment les mèmes permettent une critique des impérialismes culturels - Thibaut Vaillancourt (Les Cahiers ALHIM)
According to a conception of stereotypes at the crossroads of the works of Pierre Klossowski (1970; 1984) and Roland Barthes (1957), their heuristic, social, and ideological dimensions appear more explicitly. The stereotypical representations that apply to so-called Latin America and that are conveyed in audiovisual cultures (music, cinema, television) are experiencing a reappraisal thanks to the Internet. More precisely, the computer is to be considered from the point of view of media studies as a medium that subsumes its historical and technological predecessors. In this, the representations from the cultural industries of the 20th century find themselves digested, reenacted, and re-semanticized by the said Internet culture, of which memes are an exemplary occurrence today. Social networks as a new field of ideological, symbolic, and social struggles then appear as the vector of new representations and new stereotypes. Whether they are empirically true or false matters less than the scope and effect of the stereotypes thus produced and conveyed. The question then becomes that of knowing what the presuppositions and foundations of certain Latin American memes are, to finally ask us what geopolitical and cultural relations are at work behind problematic representations of Latin America and its inhabitants.